POLICY, INNOVATION, AND PUBLIC HEALTH: A COMPARATIVE STUDY OF HEALTH SYSTEMS IN EMERGING ECONOMIES - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This comparative study analyses health policies, reforms, and health systems performance in selected emerging economies- India, Brazil, and South Africa. The purpose is to identify each country’s approach to managing healthcare issues, adoption of innovations, and effects on health equity. Using a cross-sectional research design, the study incorporated both qualitative and quantitative data sources, including structured interviews, relevant global health reports, and key health indicators such as life expectancy, maternal mortality, immunization rates, and disability-adjusted life years (DALYs). India’s health system was characterized by a life expectancy of 74 years, maternal mortality rate of 45 per 100,000 live births, and immunization rate of 92%. Brazil with a life expectancy of 72 years had higher maternal mortality of 52 per 100,000 and immunization of 85%. South Africa, which targeted geographical coverage through mobile health facilities, has a life expectancy of 68 years, a maternal mortality ratio of 70/100,000, and immunization coverage of 80%. Challenges included limited budgets, healthcare workforce shortages, and inequitable access to healthcare, especially in rural areas. The study recommends increased budget allocations, public-private partnerships, and incentivized rural services to enhance health equity and progress toward Sustainable Development Goals.